2014
DOI: 10.1007/s12072-014-9573-1
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver reproducibility of the controlled attenuation parameter (CAP) for quantifying liver steatosis

Abstract: The results of this study show that the interreader agreement in CAP measurement is good. In healthy volunteers, the CAP is strongly correlated with age and BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 23 publications
0
29
2
Order By: Relevance
“…In contrast, the optimal cut-off value of the CAP for the diagnosis of liver steatosis varies between published studies and there is also an overlap between adjacent grades of steatosis [3].In the study of Macias et al, the patients were enrolled in two tertiary care centres and the CAP measurements were carried out by an experienced operator at each centre; thus, the inter-observer variability should also be taken into account. In a study on the inter-observer concordance in the CAP measurements by the same group, the overall intraclass correlation coefficient was 0.84 (95% confidence interval 0.77-0.88) and the absolute difference in CAP values between the two observers was 20 dB/m, which is higher than the median changes observed in this series of HIV-infected patients [4].Our group has reported that the inter-observer agreement is only fair (0.44; 95% confidence interval 0.31-0.56) for CAP values in the range found in the series of Macias et al (< 240 dB) [5]. CAP is an estimate, in dB/m, of the attenuation of the ultrasound beam as it travels through the liver tissue and it is hypothesized that, when there is a small amount of fat in the liver parenchyma, the back-scattering -which accounts for the loss of amplitude of the ultrasound waves -could be determined by small heterogeneities caused by tiny blood vessels rather than by the fat droplets [5].The real clinical value of the changes in the CAP values over a 12-month period observed in the series of Macias et al remains to be established.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…In contrast, the optimal cut-off value of the CAP for the diagnosis of liver steatosis varies between published studies and there is also an overlap between adjacent grades of steatosis [3].In the study of Macias et al, the patients were enrolled in two tertiary care centres and the CAP measurements were carried out by an experienced operator at each centre; thus, the inter-observer variability should also be taken into account. In a study on the inter-observer concordance in the CAP measurements by the same group, the overall intraclass correlation coefficient was 0.84 (95% confidence interval 0.77-0.88) and the absolute difference in CAP values between the two observers was 20 dB/m, which is higher than the median changes observed in this series of HIV-infected patients [4].Our group has reported that the inter-observer agreement is only fair (0.44; 95% confidence interval 0.31-0.56) for CAP values in the range found in the series of Macias et al (< 240 dB) [5]. CAP is an estimate, in dB/m, of the attenuation of the ultrasound beam as it travels through the liver tissue and it is hypothesized that, when there is a small amount of fat in the liver parenchyma, the back-scattering -which accounts for the loss of amplitude of the ultrasound waves -could be determined by small heterogeneities caused by tiny blood vessels rather than by the fat droplets [5].The real clinical value of the changes in the CAP values over a 12-month period observed in the series of Macias et al remains to be established.…”
contrasting
confidence: 54%
“…In a study on the inter-observer concordance in the CAP measurements by the same group, the overall intraclass correlation coefficient was 0.84 (95% confidence interval 0.77-0.88) and the absolute difference in CAP values between the two observers was 20 dB/m, which is higher than the median changes observed in this series of HIV-infected patients [4].Our group has reported that the inter-observer agreement is only fair (0.44; 95% confidence interval 0.31-0.56) for CAP values in the range found in the series of Macias et al (< 240 dB) [5]. CAP is an estimate, in dB/m, of the attenuation of the ultrasound beam as it travels through the liver tissue and it is hypothesized that, when there is a small amount of fat in the liver parenchyma, the back-scattering -which accounts for the loss of amplitude of the ultrasound waves -could be determined by small heterogeneities caused by tiny blood vessels rather than by the fat droplets [5].The real clinical value of the changes in the CAP values over a 12-month period observed in the series of Macias et al remains to be established. References 1 Mac ıas J, Real LM, Rivero-Ju arez A et al Changes in liver steatosis evaluated by transient elastography with the controlled attenuation parameter in HIV-infected patients.…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…CAP has a number of advantages when compared to other common measures: Providing an instantaneous assessment of liver steatosis, quantificational accuracy and ease of performance, as well as inexpensive cost and reproducibility [24,25]. CAP is also an operator-friendly technique with a high inter-rater reliability concordance correlation coefficient value of 0.82 [26]. Comparing CAP to the conventional ultrasound-based Hamaguchi steatosis scoring system, Carvalhana et al [27] reported a correlation of r = 0.75, p < 0.001, between ultrasound and CAP.…”
Section: Methodsmentioning
confidence: 99%
“…In that regard, MRI-PDFF is precise and can detect small changes in hepatic steatosis over time. 35 In contrast, although CAP is reproducible on repeated testing, 36 further longitudinal studies should clarify its performance as a monitoring tool.…”
Section: Performancementioning
confidence: 99%